Al-Qadi Abd Al-Jabbar: Suatu Biografi - Ibrahim, Mohd Radhi (Jurnal Usuluddin, 2001)
The aim of this article is to introduce al-Qadi ’Abd al-Jabbar’s background as one of the most prominent Islamic Rationalists of his time and his contributions to Islamic Intellectual Heritage.